Aroma Determination of Three Freshly Squeezed Strawberry Juice Based on E-nose, HS-SPME-GC-MS and GC-IMS - Jingwen ZHANG; Leiqing PAN; Kang TU (Shipin gongye ke-ji, 2023)
Flavor of different freshly squeezed strawberry juice is quite different, and its characteristics will directly affect the economic value of freshly squeezed juice. In order to explore the differences of volatile organic compounds (VOCs) in Miaoxiang No. 3 (MX3), Hongyan (HY) and Qianmei No. 2 (QM2) strawberry freshly squeezed juice, VOCs were detected by electronic nose (E-nose), headspace solid phase micro extraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) and gas chromatography-ion mobility spectrometry (GC-IMS) qualitatively and quantitatively. The results showed that contents and species of VOCs in three freshly squeezed strawberry juice were significantly different. E-nose could distinguish these three freshly squeezed strawberry juice in terms of aroma characteristics. 89 kinds of VOCs were detected by HS-SPME-GC-MS, including 55 esters, 9 aldehydes, 7 alcohols, 13 ketones and 5 acids. Among them, 22 kinds of VOCs were common to MX3, HY and QM2 strawberry freshly squeezed juice, including 11 kinds of esters, 4 kinds of aldehydes, linalool, 5 kinds of ketones and nonanoic acid. Content of 5-hexyldihydro-2(3H)-furanone in MX3 strawberry freshly squeezed juice was higher, while contents of hexyl acetate and (Z)-2-hexen-1-ol acetate in HY strawberry freshly squeezed juice were higher. Methyl acetate, methyl butyrate, methyl hexanoate, hexanal, (E)-2-hexenal, linalool and 4-methoxy-2,5 dimethyl-3(2H)-furanone in QM2 strawberry freshly squeezed juice were higher. 60 kinds of VOCs were identified by GC-IMS, including 24 esters, 12 aldehydes, 7 alcohols, 10 ketones, 2 furans and 5 others. Contents of ethyl butyrate, isopropyl acetate, 2-hexenal and 1-penten-3-ol were higher in the three freshly squeezed strawberry juice, which were regarded as the key VOCs for the formation of flavor characteristics in freshly squeezed strawberry juice.